La Gestion du Risque de Micro-crédit: La Nécessité du Diagnostic Financier: Cas de la PME MIGEG Microfinance S.A. - Lucas Pony (European Scientific Journal, ESJ, 2017)
The reduction of the losses related to credit outstanding payment is very necessary in the micro finance institutions in general, and the SME of micro finance MIGEG* S.A in particular. Here, we carried out a study concerning the management of micro credits risk which result to losses due to non-refund. The method that was proposed in this study is that of the financial diagnosis which operates in two phases. The first phase involves the use of the data collected during the interview to analyze the morality of the customer (Phase 1), while the second phase involves the use of the financial and accounting quantitative data to analyze the financial health of the customer (Phase 2).The diagnosis method considered is that of Dupont which allows us to considerably reduce the percentage of credits outstanding payment. Consequently, it also helps to improve the company’s funds. The proposed method will help the managers to detect the risks of application for credit. The bank will thus grant only the credit bonds related to the highest refunds. This, however, will further lead to the following results: For MIGEG S.A to be viable, it must insist on the ratio of the assets. This refers to the sales of the credits to promote refunds without risk. On the other hand, MIGEG S.A will insist on the ratio of the financial lever, debt and assets, in order to promote the prefinancing of the risk credits. Therefore, it will help to avoid credits related to the guarantees such as the land certificate, inheritance etc.